Scenario planning, an evolution of practice - Ratcliffe, John (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
Scenario Planning is fast becoming one of the most popular and persuasive tcchniques, used in strategic planning and foresighting cxercises of all kinds in both public and private sectors, It is likely that the approach will play a more prominent role in helping organisations and agencies from all parts of the economy, governance and society in Ireland think, talk, act and plan differently collaboratively and creatively over the next few years. Whilst the field of urban studies has been slow to recognise and adopt a 'futures' approach using techniques such as scenario planning this is starting to change.
Keywords: Urban geography -- Ireland